2008
DOI: 10.1007/s00431-008-0737-7
|View full text |Cite
|
Sign up to set email alerts
|

Continuation of metformin in the first trimester of women with polycystic ovarian syndrome is not associated with increased perinatal morbidity

Abstract: This study aimed to assess the perinatal outcome, especially foetal growth, following the continuation of metformin during the first trimester of pregnancy. All women with polycystic ovary syndrome (PCOS) treated with metformin in the first trimester and who delivered a baby weighing 500 g or more between 2003 and 2005 were studied. Subjects were matched for age and parity with randomly selected controls. The perinatal outcomes studied were: growth parameters, gestational age, congenital defects, hypoglycaemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 17 publications
(21 reference statements)
3
26
0
1
Order By: Relevance
“…Our results support the idea that metformin has no significant reduction to GDM, consistent with some retrospective studies [43,44]. But it is different from other studies [36,38,45], which may partially be based on the non-randomized experiment and unconventional criteria, such as the measurement of postprandial glycemia or fasting glycemia, which has a very low sensitivity for the diagnosis of diabetes and may impair the diagnostic accuracy.…”
Section: Discussionsupporting
confidence: 83%
“…Our results support the idea that metformin has no significant reduction to GDM, consistent with some retrospective studies [43,44]. But it is different from other studies [36,38,45], which may partially be based on the non-randomized experiment and unconventional criteria, such as the measurement of postprandial glycemia or fasting glycemia, which has a very low sensitivity for the diagnosis of diabetes and may impair the diagnostic accuracy.…”
Section: Discussionsupporting
confidence: 83%
“…Subsequent to this meta-analysis, a retrospective study has examined a wider array of perinatal outcomes in metformin-treated and control pregnancies, matched for age and parity. Neonatal growth deficits, congenital defects, hypoglycemia, and neonatal unit admission were found to be either comparable between groups or less common in the metformin-treated group (122).…”
Section: Metformin In Pcosmentioning
confidence: 98%
“…Neonatal hypoglycemia was also less commonly reported in the metformin group with fewer babies requiring intravenous glucose therapy. [13] Metformin is excreted in breast milk, but the amount secreted is clinically insignificant and there have been no reported adverse effects on breastfed infants with mothers who take metformin. [14] A study which measured growth, motor-social development and illness in 61 nursing infants (21 males and 40 females) and 50 formula-fed infants (19 males and 31 females) born to 92 mothers with PCOS who were taking metformin (median of 2.55 gm/day) throughout pregnancy and lactation, reported that none of the children had any delay in either growth or in developmental milestones.…”
Section: Review Of Literaturementioning
confidence: 99%